Causes of Revelations in View of the Classical Scholars and Post-Classical Scholars - Faheem Ullah; Dr. Abdul Qadoos (Corresponding Author) (Journal of Religion and Society, 2025)
This article explores the differing perspectives of early (متقدمین) and later (متاخرین) Islamic scholars on the concept of Asbāb al-Nuzūl (causes of Qur’anic revelation). The early scholars, primarily from the first three centuries of Islam, relied heavily on transmitted reports (Riwāyāt) from the Companions and their Followers without engaging in extensive analytical critique. Their methodology focused on preserving narrations with minimal interpretation or contextual analysis. In contrast, the later scholars adopted a more critical and investigative approach. They not only examined the chains of transmission (Isnād) but also applied principles of textual analysis (Dirāyah), historical context, and linguistic reasoning. These scholars, such as al-Wāhidī and al-Suyūṭī, produced comprehensive works that systematized and evaluated various reports on the occasions of revelation. The article highlights this methodological evolution, illustrating the transition from purely narrative transmission to a more holistic, scholarly framework in understanding Qur'anic revelation. Keywords: Qur’anic revelation, Mutqaddimīn (Classical Scholars), Muta’akhkhirīn (Post-Classical Scholars), Narrated reports (Riwāyāt), Isnād (chain of Transmission), Dirāyah (Textual analysis), Historical context, Linguistic reasoning, Methodological evolution